Money Yield Tables for Sal with Particular Reference to Chanti Depot of Changbhakhar Division (Madhya Pradesh) - Suri, S. K. (Indian Forester, 1976)
Based on the auction results of Chanti depot for the year 1973-74 and the prevalent logging and haulage rates of Changbhakhar Forest Division, stumpage values of mid girth class trees of sal for various leads have been calculated. Using these stumpage values and all India yield tables for Sal of site qualities II, III and IV, money yield tables on per hectare basis have been constructed, presented and their scope and usefulness discussed.